Factors associated with thermal injury of abdominal skin in focused ultrasound ablation of uterine fibroids - Tang Chendian; Huang Guohua; Zhibiao Wang; Liu Fang; Shuang Luo; Xiaofang Liu; Qiuling Shi (International Journal of Hyperthermia)
Objective To investigate the factors which may cause thermal injury of abdominal skin in patients with uterine fibroids (UFs) who underwent ultrasound-guided focused ultrasound ablation surgery (FUAS).Method A total of 123 patients were enrolled in the injury group. In contrast, 246 patients without thermal injury were assigned to the non-injury group. The relationship between patient and treatment parameters and injury were explored using univariate analysis and multiple logistic regression analyses. In addition, the factors influencing the degree of thermal injury were analyzed using Kruskal–Wallis H.Results (1) Abdominal scars (p = .007, OR = 2.187, 95% CI: 1.242–3.849), abdominal wall thickness (p < .001, OR = 1.042, 95% CI: 1.019–1.067), fundus fibroids (p = .038, OR = 1.790, 95% CI: 1.033–3.100), UFs with hyperintense/mixed T2-weighted imaging (T2WI) signals (p = .022, OR = 1.843, 95% CI: 1.091–3.115), average sonication power (AP) (p = .025, OR = 1.021, 95% CI: 1.003–1.039), and treatment time (TT) (p < .001, OR = 1.017, 95% CI: 1.011–1.023) were independent risk factors for thermal injury, while treatment volume (TV) (p = .002, OR = 0.775, 95% CI: 0.661–0.909) was a protective factor for injury. (2) Four groups were subdivided according to the degree of thermal injury(Group A: without skin injury. Group B: with changed T2WI signal in the abdominal wall, Group C: mild skin injury, Group D: severe skin injury), comparison of each with every other showed that the abdominal wall in Groups A and D was thinner than Groups B and C, with statistically significant differences (PAB<0.05, PAC<0.01, PDC<0.05, PDB<0.05); Group A was slightly thicker than D, however, without statistical difference. The ratio of sonication time (ST) to TV in Group A was the lowest of all (PAB, PAC, PAD all < 0.05). And as the level of thermal injury rose, the ratio gradually increased, however, without statistical difference.Conclusions Based on our limited results, the following conclusion was made. (1) Abdominal scars, abdominal wall thickness, fundus fibroids, UFs with T2WI hyperintense/mixed signals, AP and TT were independent risk factor. (2) Neither too thick nor too thin abdominal walls would be recommended, as both might increase the risk of skin injury. (3) Noticeably, the risk of skin injury might increase considerably when the ST was longer and the sonication area was more fixed.